INTERAKSI SOSIAL FORUM MAHASISWA KOTA TIDORE KEPULAUAN DI KOTA MANADO - Maradjabessy, M. Fandi; Lasut, Jouke J.; Lumintang, Juliana (Universitas Sam Ratulangi, 2019)
Organization or Forum as container where people get together, work together in a rational and systematic, in utilizing the resources of the Organization efficiently and effectively to achieve the objectives that have been determined. Cooperation was generally done by following the pattern of interactions between any individual or group to interact within and outside the organization. Interaction patterns are aligned with different rules, norms, beliefs, certain values as set forth the Organization's interaction patterns within a specified time will form a habit or form joint cultural organization always control the members of the organization. Student Forum of Tidore Islands City (FOMAKATI) is also a social organization of the region is the city of Manado. This organization is students of Tidore Islands City origin study in Manado City founded an organization of associations. This Forum was created to be shared between interaction containers among the students of Tidore Islands City during a study in Manado. FOMAKATI is an organization that consists of various individuals who have diverse backgrounds. This then makes the contradiction or conflict fought fellow members. The conflicts that occur in the FOMAKATI seen in the miscommunication and the separation of certain positions based on the difference in views and interests when the process of deliberation the turn of Chairman. The separation of the strongholds as mentioned by stewards and members due to ego-ego Group organization incorporated in Cipayung returning compete to snatch an important position in FOMAKATI. The process of conflict resolution in FOMAKATI i.e. Trustees hold meetings and meetings in order to unravel the conflict. Â Keywords: interaction, FOMAKAT